PENGARUH KEMANDIRIAN BELAJAR DAN KOMPETENSI DOSEN TERHADAP MOTIVASI BELAJAR MAHASISWA (Study Kasus di Program Studi Manajemen UNISLA): The Effect Of Learning Independence And Lecturers Competency Towards Students' Learning Motivation (Case Study at the UNISLA Management Study Program) - Nanto Purnomo (UIR Press, 2021)
The big challenge in the world of education during the Covid 19 pandemic is overcoming the difficulties of implementing online learning, and what is equally important is building and increasing student motivation during the Covid 19 pandemic. Having good motivation in learning will show good results so that in expect an increase in the quality of learning as mandated by the National Education System Law Number 20 of 2003 national education which aims to educate the nation's life and improve the quality of learning This type of research is descriptive quantitative research. The sampling technique used is simple random sampling. The population in this study were students of Unisla management study program. Data collection techniques used a questionnaire using a Likert scale. The analysis tools used were validity and reliability analysis to determine the reliability of a questionnaire used in the study. In this study also used correlation analysis, multiple regression analysis, t test and F test assisted by the IBM SPSS Statistics version 25 software for windows. The results showed that the learning independence variable partially had a positive and significant effect on the learning motivation variable. The lecturer competence variable partially has a positive and significant effect on the learning motivation variable. The variables of independent learning and lecturer competence simultaneously have a significant influence on student learning motivation variables. The percentage of the influence of the independent learning variable and lecturer competence on student learning motivation shows a value of 72.2% and the remaining 27.8% is influenced by variables other than variables X1 and X2.